ANALYSIS OF INCOME AND FEASIBILITY OF PEPPER FARMING (Piper Nigrum L.) IN PATTONGKO VILLAGE, CENTRAL SINJAI DISTRICT - Makmur; Alfira; Muhammad Amar; Sitti Fatimah; Akriandi Amin; Fajaruddin Fajaruddin (AgriMu, 2026)
This study aims to analyze the income and feasibility of pepper (Piper nigrum L.) farming in Pattongko Village, Sinjai Tengah District, Sinjai Regency. This study uses a quantitative method with a survey approach. The study population is all 31 pepper farmers in Pattongko Village and all of them are sampled using a saturated sampling technique. The research data consists of primary and secondary data. Primary data was obtained through direct observation, interviews, questionnaires, and documentation from pepper farmers. Meanwhile, secondary data was obtained from the Central Statistics Agency (BPS), the Sinjai Regency Agriculture Service, and various relevant literature sources. Data analysis was carried out using production cost analysis, revenue, income, and farm feasibility analysis using the Revenue Cost Ratio (R/C Ratio) approach. The results of the study indicate that the average production cost of pepper farming consists of fixed costs and variable costs. Variable costs are the largest cost component, including the costs of fertilizer, pesticides, and labor. Meanwhile, farmer income is obtained from pepper production which is sold based on the prevailing market price. This income is influenced by the relatively high selling price of pepper at the farmer level. The feasibility of the farming business based on the R/C Ratio shows a value of 7.50, indicating that pepper farming is feasible. The B/C ratio is 6.50, with a break-even price of Rp 15,584/kg and a production break-even point of 11 kg. A sensitivity analysis shows that pepper farming in Pattongko Village is highly resilient to changing conditions, both in terms of decreasing selling prices and increasing production costs.